C-Reactive Protein as A Fungal Infection Marker in Acute Leukemia Patients - Brigitte Rina Aninda Sidharta; JB. Suparyatmo; Avanti Fitri Astuti (Indonesian Association of Clinical Pathologist and Medical laboratory, 2021)
Invasive Fungal Infections (IFIs) can cause serious problems in cancer patients and may result in high morbidity andmortality. C-reactive protein levels increase in response to injury, infection, and inflammation. C-reactive protein increasesin bacterial infections (mean of 32 mg/L) and in fungal infections (mean of 9 mg/L). This study aimed to determineC-Reactive Protein (CRP) as a marker of fungal infections in patients with acute leukemia by establishing cut-off values ofCRP. This study was an observational analytical study with a cross-sectional approach and was carried out at the Departmentof Clinical Pathology and Microbiology of Dr. Moewardi Hospital in Surakarta from May until August 2019. The inclusioncriteria were patients with acute leukemia who were willing to participate in this study, while exclusion criteria were patientswith liver disease. There were 61 samples consisting of 30 male and 31 female patients with ages ranging from 1 to 70 years.Fifty-four patients (88.5%) were diagnosed with Acute Lymphoblastic Leukemia (ALL) and 30 (49.18%) were in themaintenance phase. The risk factors found in those patients were neutropenia 50-1500 μL (23.8%), use of intravenous line(22%), and corticosteroid therapy for more than one week (20.9%). The median of CRP in the group of patients with positiveculture results was 11.20 mg/L (11.20-26.23 mg/L) and negative culture results in 0.38 mg/L (0.01-18.63 mg/L). The cut-offvalue of CRP using the Receiver Operating Curve (ROC) was 9.54 mg/L (area under curve 0.996 and p. 0.026), with a sensitivityof 100%, specificity of 93.2%, Positive Predictive Value (PPV) of 33.3%, Negative Predictive Value (PPV) of 100%, PositiveLikelihood Ratio (PLR) of 1.08, Negative Likelihood Ratio (NLR) of 0 and accuracy of 93.4%. C-reactive protein can be used asa screening marker for fungal infections in patients with acute leukemia.